Determination of ethyl glucuronide, a minor metabolite of ethanol, in human serum by liquid chromatography-electrospray ionization mass spectrometry - Nishikawa, Mayumi; Tsuchihashi, H.; Miki, A.; Katagi, M.; Schmitt, Georg; Zimmer, Holger; Keller, Thomas; Aderjan, Rolf (Journal of chromatography, 1999)
A rapid and sensitive determination procedure using liquid chromatography-electrospray ionization mass spectrometry (LC-ESI-MS) has been developed for the determination of ethyl glucuronide (EtG) in human serum. Samples were precipitated with methanol, centrifuged and the supernatant was evaporated to dryness followed by reconstitution with distilled water. As mobile phase 30 mM ammonium acetate-acetonitrile (30:70, v/v) was utilized. The base peak observed at m/z 221 was the [M−H]− ion of EtG, which was detectable in satisfactory sense. The detection limit was 0.03 μg/ml in the selected ion monitoring mode. A calibration graph constructed for EtG in serum gave good linearity over the range from 0.1 to 25 μg/ml. This paper also presents the application of this LC-ESI-MS procedure to the analysis of authentic serum samples.